Demands and Job Resources in the Child Care Workforce: Swiss Lead Teacher and Assistant Teacher Assessments. Issue 7 (2nd October 2016) - Bloechliger, Olivia R.; Bauer, Georg F.
ABSTRACT: Center-based child care has been struggling with poor health and high turnover rates of child care staff and their adverse impact on care quality for decades. Yet little is known about personal and structural antecedents of job resources and job demands that are valid predictors of health and turnover in the child care workforce. Research Findings : This study investigated job resources and job demands among child care staff of different education levels (491 lead teachers and 310 assistant teachers) from Switzerland. Results from t -tests and hierarchical regression analyses indicated slightly higher job resources and job demands for lead teachers than for assistant teachers but similar antecedents of job resources and job demands. Overall, center characteristics shaped job resources and job demands more strongly than staff characteristics. More specifically, job resources were predicted by structural characteristics associated with professionalism in child care work, whereas job demands were primarily dependent on adequate staffing. Practice or Policy : The findings suggest that center characteristics (e.g., work environment and staffing levels) should be targeted in order to increase job resources and reduce job demands, which would in turn promote health and lower turnover rates among child care staff.